2014
DOI: 10.1139/cgj-2013-0374
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the resistance profile of a spudcan penetrating sand overlying clay

Abstract: Assessment of the risk of punch-through failure of spudcan foundations on sand overlying clay requires prediction of the full penetration resistance profile, from touchdown and through punch-through to equilibrium of the vertical resistance at depth in the underlying clay layer. This study uses the Coupled Eulerian–Lagrangian approach, a large deformation finite element analysis method, to model the complete penetration resistance profile of a spudcan on sand overlying clay. The sand is modeled using the Mohr–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
76
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(77 citation statements)
references
References 24 publications
(48 reference statements)
1
76
0
Order By: Relevance
“…In contrast to RITSS and EALE, an element in CEL may be occupied by multiple materials fully or partially, with the material interface and boundaries approximated by volume fractions of each material in the element. The CEL method has been used by a number of researchers to investigate the penetration of spudcan foundations in various soil stratigraphies [27,35,36,25,12] and uplift capacity of rectangular plates [9]. The comparatively rigid structural part (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to RITSS and EALE, an element in CEL may be occupied by multiple materials fully or partially, with the material interface and boundaries approximated by volume fractions of each material in the element. The CEL method has been used by a number of researchers to investigate the penetration of spudcan foundations in various soil stratigraphies [27,35,36,25,12] and uplift capacity of rectangular plates [9]. The comparatively rigid structural part (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…A 'general contact' algorithm by means of an enhanced immersed boundary method describes frictional contact between Lagrangian and Eulerian materials. Advanced soil constitutive models, such as a hypoplastic model for sand, a visco-hypoplastic model for clay and a modified Tresca model considering strain softening and rate-dependency of clay, have been incorporated into the CEL [27,26,12]. To date, CEL is limited to total stress analysis, although it can be modified to obtain pore pressures under undrained conditions [50].…”
Section: Introductionmentioning
confidence: 99%
“…Simulations focusing on the soil-structure interaction problems have been carried out by Tho et al [29], Qiu et al [24] [25] and Hu et al [13]. They revealed that the CEL approach is well suited to solving numerical problems involving large deformations which cannot be solved satisfactorily using the classic finite element method.…”
Section: Numerical Methods 31 Coupled Eulerian-lagrangian (Cel) Methodsmentioning
confidence: 99%
“…The contact pressure between Eulerian and Lagrangian materials is calculated by a penalty contact method, while the shear stress τ is calculated by the Coulomb frictional frame, i.e., τ = µ c σ. µ c is the frictional coefficient and σ is the contact pressure. The CEL method was wildly utilized to solve geotechnical problems with large deformations (Qiu et al, 2011;Tho et al, 2013;Hu et al, 2014;Liu et al, 2014;Dutta et al, 2015;Kim et al, 2015;Liu, 2015, 2016;Liu et al, 2016). More information about the CEL method can be found in (Dassault Systemes, 2010;Benson, 1992).…”
Section: Large Deformation Finite Element Analysismentioning
confidence: 99%